Translation-mediated communication in a digital world : facing the challenges of globalization and localization - O'Hagan, Minako, 1959- (Topics in translation, 2002)
Annotation The Internet is accelerating globalization by exposing organizations and individuals to global audiences. This in turn is driving teletranslation and teleinterpretation, new types of multilingual support, which are functional in digital communications environments. The book describes teletranslation and teleinterpretation by exploring a number of key emerging contexts for language professionals.